A review on household air pollution and biomass use over Kenya - Zablon Weku Shilenje; Zablon Weku Shilenje; Scholastica Maloba; Victor Ongoma (Frontiers in Environmental Science, 2022)
Household air pollution (HAP) causes multiple noncommunicable diseases, such as pneumonia, stroke, and ischemic heart disease, and is responsible for over 3.8 million deaths globally per year. Kenya has a high rate of HAP, mainly caused by solid fuels. This review assesses its effect and identifies factors that could improve policy in Kenya. A systematic review approach is used, mainly considering 88 research articles on the Web of Science, published from 1951 to 2022. We excluded studies on HAP caused by other forms of fuel, subjective study types, and studies focusing on animals. The results show that rural settings and urban slums have more HAP, ventilation is an important factor, HAP is high in the evening, and children and women health is significantly affected. There is a need for interventions to reduce the use of biomass fuels in Kenya. The interventions include improved access to efficient cookstoves with ventilation, community health awareness about ventilation, housing rules for better ventilation in rural and urban areas, and NGO partnership for improving access to improved cookstoves in rural areas. The government’s role includes subsidizing the supply and cost of renewable energy and adopting energy policies that encourage populations to switch to more efficient cookstoves, cleaner energy, and modern biofuels.